Characterization & Antibacterial Activity of Curcumin-Nanostructured Lipid Carrier - Rabima Rabima (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2018)
The aim of this study is to formulate curcumin into Nanostructured-Lipid Carrier preparations as an effort to improve bioavailability of curcumin, determined its characterization and to study its antibacterial activity. The method used to synthesis curcumin-NLC is evaporation and diffusion of solvents in the aqueous system and ultrasonication, oleic acid and cholesterol are used as liquid lipid and solid lipid matrices. Curcumin-NLC was characterized by parameters of polydispersity index (IP), particle size, potential zeta, entrapment efficiency and drug loading.The curcumin-NLC produced in this study had an average particle size of 17,4 nm, polidispersity index (IP) 0,574, zeta potential -63,43 mV, entrapment efficiency and drug-loading are 92,23% and 0,87% respectively. These results indicate that curcumin can be formulated as an NLC with good characteristics and potential to be developed as an effective drug delivery systems. The inhibition zone of curcumin-nlc against S.aureus and E.coli obtained from this study are 7,72 mm and 6,0 mm respectively, and minimum inhibition concentration (MIC) is 50%. Keywords: Antibacterial, Bioavailabilty, Curcumin, NLC